Impact on railway track of cars with increased axle load - V. V. Tret’Yakov; I. B. Petropavlovskaya; V. O. Pevzner; T. I. Gromova; I. V. Tret’Yakov; K. V. Shapet’Ko; I. S. Smelyanskaya; A. S. Tomilenko (Вестник Научно-исследовательского института железнодорожного транспорта, 2016)
Solving the problem of development of growing volume of traffic in the absence of reserves of available and actual capacity on a number of areas and entire directions necessitates continuous increase of train weight, as well as the use of cars with increased axle load. axle load 25 tonnes wagons is officially adopted in 2013 in Russian railways as the standard. The question of operating cars with axle load 27 tonnes is considered. Comprehensive tests have been started from 2014 at the section of the Oktyabr’skaya Railway Kovdor - Murmansk including evaluation of performance and interaction of the track and cars with axial load of 25 and 27 tonnes in trains of different mass and monitoring the accumulation of track deterioration at the volume of traffic at the level of 10 % in cars with axle load of 27 tonnes with loading capacity at around 14.6 million tonnes gross per year. In these tests was introduced a new element to determine absolute track settling against benchmarks installed out of the track, with the help of high-precision geodetic equipment. Research will be continued in 2016, but already now we can state the following: 1. With the introduction into circulation of heavy trains, including rolling stock of new mass with increased axial loads, it is necessary to evaluate not only the strength of the elements of track superstructure by the first limiting state, but also the intensity of the deterioration in track in general by second limiting state. 2. Handling of heavy train, including cars that have increased axial load, it is advisable to arrange circular routes with corresponding adjustment to the costs on current maintenance and repair of tracks. 3. Factors that take into account the presence of heavy trains and rolling stock with increased axial loads, should be included in the standard documentation, determining the cost of current maintenance of track, including the number of track servicemen, as well as the volumes of repairs.